INDIVIDUO: Results from a patient-centered lifestyle intervention for obesity surgery candidates. Issue 4 (July 2017) - Camolas, José; Santos, Osvaldo; Moreira, Pedro; do Carmo, Isabel
Summary: Background: Preoperative nutritional counseling provides an opportunity to ameliorate patients' clinical condition and build-up adequate habits and perception of competence. Study aimed to evaluate: (a) the effect of INDIVIDUO on weight and metabolic control; (b) the impact of INDIVIDUO on psychosocial variables associated with successful weight-control. Methods: Two-arms randomised controlled single-site study, with six-month duration. Patients were recruited from an Obesity Treatment Unit's waiting list. For the intervention group (IG), an operating procedure manual was used, nutritionists received training/supervision regarding INDIVIDUO's procedures. Control group (CG) received health literacy-promoting intervention. Intention-to-treat and per-control analysis were used. Outcomes included weight, metabolic control variables (blood pressure, glycemia, insulinemia, triglycerides, cholesterol), measures of eating and physical activity patterns, hedonic hunger, autonomous/controlled regulation, perceived competence for diet (PCS-diet) and quality of life. Primary outcomes were weight and metabolic control. Effect size was estimated by odds ratio and Cohens'd coefficient. Results: Overall, 94 patients participated (IG:45; CG:49) and 60 completed the study (IG:29; CG:31). Intervention patients lost an excess 9.68% body weight (%EWL), vs. 0.51% for CG. Adjusting for age and baseline BMI, allocation group remained an independent predictor of %EWL ( B = 8.43, 95%CI: 2.79–14.06). IG had a six-fold higher probability (OR: 6.35, 95%CI: 1.28–31.56) of having adequate/controlled fasting glycemia at final evaluation. PCS-diet at final evaluation was independently predicted by baseline PCS-diet ( B = 0.31, 95%CI: 0.06–0.64), variation in autonomous regulation ( B = 0.43, 95%CI: 0.15–0.71) and allocation group ( B = 0.26, 95%CI: 0.04–1.36). Conclusions: Results on weight and metabolic control support INDIVIDUO as a valuable clinical tool for obesity surgery candidates counseling. Additionally, intervention associated with perceived competence for weight-control behaviours and autonomous regulation.